- IMPLEMENTASI AKHLAK AL KARIMAH DI DALAM EKONOMI ISLAM: - - Mustofa Tohari; Ary Fatkurrochman Ariansyah; Zikri Rahmani Rahmani (Jurnal Bilqolam Pendidikan Islam, 2024)
Economic development and the business world are increasingly sophisticated and no longer limited by distance and time. In this era of growing technological developments, it is hoped that the business carried out by each individual will continue to run well and without obstacles. In reality, problems arise ranging from harmful business models, deceptive business methods and legalising all means, being too capitalist and having no impact on social welfare. This research uses library research and has theories used to explain and conclude the issues raised in this research. The data source of this research is secondary data. Secondary data is data that researchers obtain from literature reviews, books, articles, magazines, and so on that are relevant to this research. The results of this study indicate that ethics in business is something very important and must be a guideline for every business person. The Quran mentions many ethical concepts that can be applied and adopted in the business world. This research is expected to be a reference, especially guidance in the business world. How Islam regulates all aspects of human life even in economic activities, especially business.